Antimonene dendritic nanostructures: Dual-functional material for high-performance energy storage and harvesting devices. (November 2020) - Mariappan, Vimal Kumar; Krishnamoorthy, Karthikeyan; Pazhamalai, Parthiban; Natarajan, Subramanian; Sahoo, Surjit; Nardekar, Swapnil Shital; Kim, Sang-Jae
Abstract: The development of an integrated energy devices and technologies has brought new demands for novel materials with multifunctional properties such as energy harvesting and storage. We report herein a core-shell-like hierarchical structure comprising a metal (three-dimensional (3D) Ni) core and a metalene (antimonene nanodendrite) shell that can store electrochemical energy and harvest energy via triboelectrification. Antimonene/3DNi nanostructures were fabricated via a facile, cost-effective electrochemical deposition technique. X-ray photoelectron spectroscopy and Raman mapping analysis revealed the growth of antimonene nanostructures less than 20 nm thick on the 3D Ni foam. Electrochemical studies established a high specific capacity of 1618.41 mA h g –1 (6854.45 F g –1 ) for the antimonene/3DNi electrode, which is superior over the reported Ni-foam based binder-free electrodes. The antimonene/3DNi electrode was used as a positrode in the fabrication of an asymmetric supercapacitor (ASC) with graphene based negatrode that provide a high energy density (84.79 Wh kg –1 ) and power density (20625 W kg –1 ). Kelvin probe force microscopy studies established that the antimonene/3DNi behaved as a positive-type tribo layer. It was then used in Sb-triboelectric nanogenerator device with Kapton as the negative tribo-layer to harvest a maximum output of 54 V and 0.87 μA with a peak power of 15 μW. The exceptional energy storage and harvesting properties of the antimonene/3DNi nanostructures were confirmed in a self-charging power system using a commercial capacitor and an ASC. This proof-of-concept will stimulate further research into using metalenes in next-generation energy devices. Graphical abstract: Image 1 Highlights: Dendrite like antimonene/3DNi nanostructures were fabricated via a facile electrochemical deposition technique (cost-effective method over demonstrated ones). XPS and Raman mapping analysis revealed the growth of antimonene nanostructures on 3D Ni foam with thickness less than 20 nm. The electrochemical studies showed the high specific capacity of 1618.41 mA h g -1 (=6854.45 F g -1 ) for antimonene/3D-Ni electrode (superior over reported Ni-foam based binder-free electrodes). Asymmetric supercapacitor (ASC) device exhibit remarkable energy density of 84.79 Wh kg -1 with ultra-high power density of (20, 625 W kg -1 ). The Sb-TENG device (using Kapton as negative layer) that can harvest a maximum of 54 V and 0.87 μA with a peak power of 15 μW, respectively.